2013
DOI: 10.1200/jco.2012.45.1278
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Multicenter Phase II Trial Comparing Two Schedules of Etirinotecan Pegol (NKTR-102) in Women With Recurrent Platinum-Resistant/Refractory Epithelial Ovarian Cancer

Abstract: Purpose Etirinotecan pegol (NKTR-102) is a unique, long-acting topoisomerase-I inhibitor with prolonged systemic exposure to SN38 (7-ethyl-10-hydroxycamptothecin), the active metabolite of irinotecan. This randomized phase II trial investigated two dosing schedules of etirinotecan pegol in patients with platinum-resistant/refractory ovarian carcinoma. Patients and Methods A total of 71 eligible patients were randomly assigned to receive etirinotecan pegol 145 mg/m2 every 14 or 21 days until progression or unac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…SN-38G concentrations were not reported in this preclinical study, but clinical results have indicated substantially higher levels of SN-38G than SN-38. Promising antitumor responses have been reported for etirinotecan pegol clinically, with dose-limiting toxicity being severe diarrhea that is not manifested until a median of 63 days from the start of therapy (32,33). Clinical studies with IMMU-132 found dose-limiting neutropenia occurring within 1 week of the start of treatment, but the incidence of severe diarrhea is greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SN-38G concentrations were not reported in this preclinical study, but clinical results have indicated substantially higher levels of SN-38G than SN-38. Promising antitumor responses have been reported for etirinotecan pegol clinically, with dose-limiting toxicity being severe diarrhea that is not manifested until a median of 63 days from the start of therapy (32,33). Clinical studies with IMMU-132 found dose-limiting neutropenia occurring within 1 week of the start of treatment, but the incidence of severe diarrhea is greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…While providing improved responses in animal models, the agent failed to provide an indication of clinical benefit (29). Etirinotecan pegol is a PEG conjugate composed of a 4-arm, branched PEG, with each arm harboring irinotecan, which has been reported to extend the halflife of SN-38 to about 50 hours (30)(31)(32)(33). Preclinical studies in rats showed etirinotecan pegol serum concentrations decreasing from about 700 to 30 mg/mL over 12 hours, with low levels ($30 ng/ mL) of both irinotecan and SN-38 detected within the first few minutes; SN-38 concentrations then remained between 10 and 20 ng/mL over 14 days (31).…”
Section: Discussionmentioning
confidence: 99%
“…The response to chemotherapy after recurrence also affected OS after recurrence. The response rates to second-line chemotherapy are generally different according to the platinum-sensitivity status: 20-25% for platinum-sensitive cases, and 10-20% for platinum-resistant cases (16,17). Our results suggested that the patients who exhibited complete or partial response to second-line regimens may become LS.…”
Section: Long-term Short-term Survivors N (%) Survivors N (%) -----mentioning
confidence: 80%
“…Grade 3/4 toxicities included dehydration (24%) and diarrhoea (23%), whereas neutropaenia was less frequent (11.3%). 56 On a side note, the study suggested the use of the TOP1 gene as a biomarker prior to treatment in order to predict sensitively and reduce potential toxicities. 53 Other NKTR-102 clinical studies include an open-label multicenter extension study of NKTR-102 in subjects previously enrolled in NKTR-102 studies (ClinicalTrials.gov identifier NCT01457118); a phase IIa/IIb multicenter open-label study to evaluate NKTR-102 in combination with cetuximab vs. irinotecan in combination with cetuximab in second-line colorectal cancer patients (ClinicalTrials.gov identifier NCT00598975); a phase II study in cancer patients with hepatic impairment to evaluate the pharmacokinetics and safety of NKTR-102 (ClinicalTrials.gov identifier NCT01991678); a phase I study of NKTR-102 in bevacizumab-resistant high grade glioma (ClinicalTrials.gov identifier NCT01663012); a phase II study in patients with relapsed SCLC (ClinicalTrials.gov identifier NCT01876446); a new phase II study in patients with second-line, irinotecan-naïve, KRASmutant colorectal cancer (ClinicalTrials.gov identifier NCT00856375); and a phase II study in NSCLC (ClinicalTrials.gov identifier NCT01773109).…”
Section: Peg Polymeric Nanoparticlesmentioning
confidence: 99%